Dynamics of a stochastic multigroup S-DI-A model for the transmission of HIV. Issue 2 (22nd January 2022) - Liu, Qun; Jiang, Daqing
ABSTRACT: This paper is concerned with a stochastic multigroup S-DI-A model for the transmission of HIV with general incidence rate. We obtain sufficient criteria for the existence and uniqueness of an ergodic stationary distribution of the positive solutions to the model by constructing a proper stochastic Lyapunov function. The stationary distribution implies that the diseases will be persistent in the long term. Some numerical simulations are introduced to illustrate our theoretical result.